Acquired haemophilia A: the importance of early recognition in cases of spontaneous bleeding in the elderly. (20th November 2014) - Patel, Neeral; Wyrko, Zoe; Naqvi, Syeda; Croft, Adam P
Abstract : We describe the case of a 79-year-old man who presented 'off legs' with acute right leg pain. He was initially treated for suspected cellulitis but subsequently found to have spontaneous soft tissue bleeding into the right thigh. He was eventually diagnosed with idiopathic acquired haemophilia A and treated with activated prothrombin complex concentrates to control acute bleeding followed by immunosuppressant therapy. Acquired haemophilia A is a potentially life-threatening and under-recognised bleeding disorder that results from the immune-mediated development of autoantibodies directed against coagulation factor VIII. The disease is more common in elderly individuals where early recognition and treatment is compounded by the presence of other comorbid conditions, including other potential causes of bleeding. These confounding factors and lack of awareness among non-specialists accounts for the delay in diagnosis that is common in this disease and contributes to the persistently high mortality in this age group.